2021
DOI: 10.1021/acsami.1c09468
|View full text |Cite
|
Sign up to set email alerts
|

Atom-by-Atom and Sheet-by-Sheet Chemical Mechanical Polishing of Diamond Assisted by OH Radicals: A Tight-Binding Quantum Chemical Molecular Dynamics Simulation Study

Abstract: Ultraflat and damage-free single-crystal diamond is a promising material for use in electronic devices such as field-effect transistors. Diamond surfaces are conventionally prepared by the chemical mechanical polishing (CMP) method, although the CMP efficiency remains a critical issue owing to the extremely high hardness of diamond. Recently, OH radicals have been demonstrated to be potentially useful for improving the CMP efficiency for diamond; however, the underlying mechanisms are still elusive. In this wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…In this case, the C–C bond breaking can be initiated through strong Si–C and O–C bonds where Si and O play as mechanically supported pilot atoms. , This event was not observed when sliding against silicon, highlighting the role of counter surfaces on the diamond polishing process. By a tight-binding quantum chemical molecular dynamics simulation, Kubo et al proposed two mechanisms of wear, i.e., atom-by-atom and sheet-by-sheet removal of diamond polishing in the presence of OH radicals acting as an oxidizing agent . In H 2 O 2 solution, it has been reported that carbon atoms can react with decomposed −H, −OH, and −O, leading to the formation of C–H, C–OH, and C–O.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this case, the C–C bond breaking can be initiated through strong Si–C and O–C bonds where Si and O play as mechanically supported pilot atoms. , This event was not observed when sliding against silicon, highlighting the role of counter surfaces on the diamond polishing process. By a tight-binding quantum chemical molecular dynamics simulation, Kubo et al proposed two mechanisms of wear, i.e., atom-by-atom and sheet-by-sheet removal of diamond polishing in the presence of OH radicals acting as an oxidizing agent . In H 2 O 2 solution, it has been reported that carbon atoms can react with decomposed −H, −OH, and −O, leading to the formation of C–H, C–OH, and C–O.…”
Section: Introductionmentioning
confidence: 99%
“…Great effort has been devoted to understanding the atomic mechanisms of chemical and mechanical polishing processes of diamond surfaces, and several mechanisms have been proposed. In particular, the sp 3 -to-sp 2 transformation has been proposed to explain the experimental observation of amorphous carbon and amorphous wear particles .…”
Section: Introductionmentioning
confidence: 99%
“…In addition to friction, the surface rubbing at high applied loads can initiate wear. Studies on diamond-like carbon films indicated that wear can be formed through the transformation from diamond-like to graphite-like carbon, which later was verified by molecular dynamics (MD) simulations by a pilot atom concept. , Furthermore, wear can be initiated under different forms of carbon including carbon chains, atom-by-atom, and carbon sheets . Under oxygenation, carbon removal can proceed through the desorption of CO or CO 2 , ,, suggesting the essential role of oxygen in the formation of wear.…”
Section: Introductionmentioning
confidence: 89%
“…MD simulation has been widely used in the field of surface engineering of single crystal nickel, copper, tungsten, aluminum, silicon, silicon carbide, aluminum nitride, gallium nitride, diamond and other materials due to its ability to simulate the nano-machining process of material systems from the perspective of atomic motion [13][14][15][16][17][18][19][20][21]. In addition, in recent years, researchers have focused on using of MD simulation to study the microscopic removal characteristics and wear mechanism of alloy materials [22,23].…”
Section: Introductionmentioning
confidence: 99%